Analysis of Ecobrick Economic Potential in Improving Community Economic Welfare: Case Study of Bukit Lawang Plantation, Kab. Langkat - Nurhalisa, Siti; Nawawi, Zuhrinal M (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
Economic potential shows the ability of economic resources produced by an area that needs to be developed to provide added value for economic development. The economic potential of the ecobrick community in the Bukit Lawang plantation village can be seen from the many economic resources generated from the utilization of ecobrick such as the construction of a recycling village and the manufacture of modular furniture crafts. With the use of ecobricks, they become goods that have economic value so that they can improve the economic welfare of the community. This study used a descriptive qualitative research method, with the data sources used in the form of primary and secondary data. Data collection techniques were used in the form of interviews, observation, and direct surveys. The research results obtained that the Bukit Lawang Plantation Village is one of the areas that utilize waste to become ecobrick as a manifestation of a creative business that can become a selling point of quality goods so that the use of ecobrick can improve the economic welfare of the community by fulfilling the needs for clothing, food, and shelter. that is needed by society. The use of this ecobrick is the result of an agreement from the community to utilize plastic waste to become a quality selling point.